The Impact of Halal Certification on MSME Actors - Mohammad Afid Syafiri; Muhammad Rozan Fikri; Khoirul Faizin (SOSIOEDUKASI, 2026)
This article aims to determine the impact of implementing Halal Certification for MSME players. The halal issue has become a global trend marked by the presence of halal certification bodies in various parts of the world. This article uses a qualitative method by reviewing relevant literature and observing the practice of implementing a halal assurance system in Indonesia. Data is obtained through journals, books, magazines, newspapers, electronic media, such as the official website of LPPOM MUI and various journals. The results showed that halal product certification has a positive impact on building a halal business in Indonesia. For consumers, halal certification provides protection, assurance, information on product halalness, and becomes an instrument of business ethics. For business actors, halal certification provides benefits to increase consumer confidence and reach the global halal food market.